Exercise Improves Outcomes of Surgery on Fatty Liver in Mice: A Novel Effect Mediated by the AMPK Pathway. Issue 2 (February 2020) - Linecker, Michael; Frick, Lukas; Kron, Philipp; Limani, Perparim; Kambakamba, Patryk; Tschuor, Christoph; Langiewicz, Magda; Kachaylo, Ekaterina; Tian, Yinghua; Schneider, Marcel A.; Ungethüm, Udo; Calo, Nicolas; et al.
Abstract : Objective: To investigate whether exercise improves outcomes of surgery on fatty liver, and whether pharmacological approaches can substitute exercising programs. Summary of Background Data: Steatosis is the hepatic manifestation of the metabolic syndrome, and decreases the liver's ability to handle inflammatory stress or to regenerate after tissue loss. Exercise activates adenosine monophosphate-activated kinase (AMPK) and mitigates steatosis; however, its impact on ischemia-reperfusion injury and regeneration is unknown. Methods: We used a mouse model of simple, diet-induced steatosis and assessed the impact of exercise on metabolic parameters, ischemia-reperfusion injury and regeneration after hepatectomy. The same parameters were evaluated after treatment of mice with the AMPK activator 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR). Mice on a control diet served as age-matched controls. Results: A 4-week-exercising program reversed steatosis, lowered insulin levels, and improved glucose tolerance. Exercise markedly enhanced the ischemic tolerance and the regenerative capacity of fatty liver. Replacing exercise with AICAR was sufficient to replicate the above benefits. Both exercise and AICAR improved survival after extended hepatectomy in mice challenged with a Western diet, indicating protection from resection-induced liver failure. Conclusions: Exercise efficiently counteracts the metabolic, ischemic, and regenerative deficits of fatty liver. AICAR acts as an exercise mimetic in settings of fatty liver disease, an important finding given the compliance issues associated with exercise. Exercising, or its substitution through AICAR, may provide a feasible strategy to negate the hepatic consequences of energy-rich diet, and has the potential to extend the application of liver surgery if confirmed in humans. Abstract : Supplemental Digital Content is available in the text